2004
DOI: 10.1515/epoly.2004.4.1.624
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chitosan-containing nanofibres by electrospinning of chitosan/poly(ethylene oxide) blend solutions

Abstract: The first successful preparation of chitosan-containing nanofibres was achieved by electrospinning of chitosan/poly(ethylene oxide) (PEO) blend aqueous solutions. The diameters of the nanofibres were in the range 40 -290 nm and decreased with increasing chitosan content and decreasing total concentration. An increase of the applied field strength leads to an increase of the diameter of the nanofibres and to a broadening of the size distribution. The possibility to prepare nanofibres containing a model drug -po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 19 publications
8
95
0
Order By: Relevance
“…The PET nanofibers have the potential to be used as blood vessels 15 while chitosan nanofibers can be used as an extracellular matrix (ECM) and in drug dosage forms. 16,17 One of the methods that introduce antibacterial activity to the PET textile can generate functional groups on to the surface of PETs by using gas plasma or formaldehyde treatment. This is subsequent to grafting antibacterial agents on to the activated surface of PETs.…”
Section: Introductionmentioning
confidence: 99%
“…The PET nanofibers have the potential to be used as blood vessels 15 while chitosan nanofibers can be used as an extracellular matrix (ECM) and in drug dosage forms. 16,17 One of the methods that introduce antibacterial activity to the PET textile can generate functional groups on to the surface of PETs by using gas plasma or formaldehyde treatment. This is subsequent to grafting antibacterial agents on to the activated surface of PETs.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated electrospun fibers were subjected for their antimicrobial activity, and results showed that blended nanofibers were found to be more effective against S. aureus and Klebsiella pneumoniae than pure PET matrices. In a similar study, Spasova et al [198] reported that electrospinning of chitosan/PEO blended solution was fabricated into nanofiber matrices and potassium 5-nitro-8-quinolinolate was incorporated into them to investigate the antimicrobial and antimycotic effect against gram-negative and gram-positive bacteria and fungi.…”
Section: Applications In Regenerative Medicinementioning
confidence: 99%
“…The authors stated that the conductivity, surface tension, and moreover the solution viscosity is what allowed for electrospinning to occur when there was a mass ratio of PEO/chitosan of 2/1 or 1/1. Spasova et al 2004;Duan et al 2004;Desai et al, 2009, reported the electrospinning of chitosan/PEO system. It was observed that as the proportion of chitosan increased, the fiber diameter was decreased.…”
Section: Electrospinning Of Chitosanmentioning
confidence: 99%